2021
DOI: 10.1364/ol.426577
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber bidirectional optical modulator derives from the microfiber coated with ITO electrode

Abstract: A cheap, compact, and simply prepared all-fiber bidirectional optical modulator based on the Pockels effect of water and the band population effect was first, to the best of our knowledge, proposed and demonstrated. The transparent conductive oxide indium-tin-oxide (ITO) was coated on the surface of a nonadiabatic microfiber and first used as a modulating electrode on the microfiber. The device was realized by just submerging the microfiber in water. With supplying an electric field perpendicular to the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Thus, this change affects the sensitive SPR and is manifested as a fast change in the spectral wavelength. Since a negative potential value is applied, a blueshift in the resonant wavelength λ SPR related to the orientation of water molecules is observed (Figure d), and the results are in agreement with those of a previous report . With the step from −1.0 to 0 V, in the reverse direction, this behavior also occurs.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, this change affects the sensitive SPR and is manifested as a fast change in the spectral wavelength. Since a negative potential value is applied, a blueshift in the resonant wavelength λ SPR related to the orientation of water molecules is observed (Figure d), and the results are in agreement with those of a previous report . With the step from −1.0 to 0 V, in the reverse direction, this behavior also occurs.…”
Section: Resultssupporting
confidence: 92%
“…Since a negative potential value is applied, a blueshift in the resonant wavelength λ SPR related to the orientation of water molecules is observed (Figure 3d), and the results are in agreement with those of a previous report. 43 With the step from −1.0 to 0 V, in the reverse direction, this behavior also occurs. When the experiment is performed in deionized water, similar results are obtained (Figure S9).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…2022, 12, 2454 2 of 12 an order of magnitude larger [13] than that of the electro-optic crystal LiNbO 3 [14,15], which has been put to practical use. In a series of subsequent studies, it was reported that the Pockels effect at the solid-liquid interface is relatively large even in hydrogenbonding solvents, such as alcohols [16], that it is small in water at the interface of noble metal electrodes, such as platinum and silver [17,18], and that an optical modulator with a practical level of signal magnitude is possible using the Pockels effect in water at the transparent electrode interface [19,20]. In the observation of the Pockels effect, an electrolyte is dissolved in the solvent to make it conductive and form an EDL, and it is known that the effect does not depend on the type of electrolyte ion [12,16].…”
Section: Introductionmentioning
confidence: 99%